STRUKTURAL ANALITIK SINTETIK (SAS) DALAM PEMBELAJARAN BAHASA INGGRIS DI MADRASAH IBTIDAIYAH - Saragih, Enny (ATTA`DIB, 2018)
Chosing the right method in teaching should be concerned by teachers in order to make the students easy to understand the lessons, but there are many teachers getting difficulties in choosing the appropriate method in teaching-learning process so that the students find difficulties in understanding the lessons. This research has been done to find out the benefit of a method called SAS (Struktural Analitik Sintetik) in teaching- learning process and the obstacles which is faced by the teacher when they apllied this method. Descriptive qualitative was applied in this research. Indept interview toward teacher of Madrasah Ibtidaiyah (MI) who have taught the students using SAS was used as technique in collecting the data. The research found, 1) SAS is a good method to be applied in teaching-learning process, it attracts the student’s interest in learning English. 2) the method guides the students to understand English easily, because they learn by doing. The obstacle which is faced by the teacher while applying the method is lack of medias. This method should be supported by various medias such as pictures and videos. Thus, it is suggested to teachers to use the method in teaching process, but it is better supported by various attractive medias in order to make the learning process more effective.